10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ObjectiveRapid Eye Movement sleep behavior disorder (RBD) is a parasomnia characterised by the loss of normal skeletal muscle atonia during REM sleep, leading to the enactment of dreams through complex motor behaviors such as talking, shouting, or violent movements that may result in injury. Emerging evidence suggests that antidepressants may be associated with RBD. This study reviewed the existing literature on the demographic and clinical features of patients with REM sleep behavior disorder (RBD) taking antidepressants, as well as the reported associations between antidepressant use and RBD.MethodsA comprehensive search strategy was implemented using the PRISMA for Scoping Reviews framework. Eligible study designs included cohort, cross-sectional, observational, randomised controlled trials, and case reports. Searches were conducted on Science Direct and PubMed for studies published between 1957 and 2025. Search terms included "REM sleep behavior disorder," "dream enactment behavior," "antidepressants," "SSRIs," "SNRIs," and "TCAs." The scoping review protocol was pre-registered on the Open Science Framework.ResultsTitle and abstract screening yielded 650 studies, with 16 studies meeting the inclusion criteria after full-text review. Data from 500 patients indicated a male predominance (70.2%), with a mean age of 53.9 years. Depression was the most common comorbidity (8 studies). SSRIs were most frequently associated with RBD (in 8 studies), followed by SNRIs (6 studies) and TCAs (6 studies).ConclusionAntidepressant-associated RBD is an emerging clinical concern requiring greater recognition and monitoring to enhance treatment outcomes. A clearer understanding of these relationships will ultimately improve risk stratification, patient counseling, and individualized treatment strategies in clinical settings.